PEMANFAATAN MEDIA PEMBELAJARAN DARING PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMK MIFTAHUL HUDA KECAMATAN NGADIROJO KABUPATEN PACITAN - NOVI MURDITA NOVI MURDITA (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2022)
ABSTRACT Utilization of online learning media is the focus of research, teachers must be able to adapt to online learning. The change in the learning process that was originally conventional has now changed to online learning. In its implementation there are obstacles both from internal and external factors. Teachers must be able to find efforts to improve the learning process. So that the results of the media used by PAI teachers are youtube, WhatsApp, google classroom. The use of learning media is less varied so that media is needed for face-to-face virtual. Constraints in the use of online learning media tend to be tired and drain energy and time, so that the efforts to implement offline learning can maximize the use of learning media. And conduct home visits as an approach to students and parents. Keywords : Learning Media, Online Learning, PAI Learning